Enhancing clay properties with eggshell powder: A sustainable alternative for soil stabilization - Munirwan, Reza Pahlevi; Taib, Aizat Mohd; Jaya, Ramadhansyah Putra; Yuliana, Yuliana; Kamchoom, Viroon (My University, 2026)
Poultry waste is increasing rapidly in many countries as urbanization and industrialization rise and create environmental and economic issues. Eggshell waste deteriorates infrastructures but could effectively stabilize clay soil. This study investigates the performance of eggshell powder (ESP) as a stabilizing agent for clay soil, emphasizing its effects on the mechanical properties of clay and its suitability for construction. The methodology involved preparing soil and ESP samples, followed by standard Proctor compaction tests, direct shear tests, and microstructural analysis. Various percentages of eggshell powder (0%, 3%, 6%, and 9%) were added to the clay soil. The results revealed that the addition of ESP improved the plasticity, compaction behavior, and shear strength of soil. The results showed that the plasticity index decreased from 30.45% (untreated soil) to 21.78% at 6% ESP, and the liquid limit reduced from 65.28% to 57.80%, enhancing soil workability and reducing swelling. Additionally, soil cohesion increased substantially from 82.7 kN/m² (untreated soil) to 144.5 kN/m² at 9% ESP, while the internal friction angle improved from 18° to 25°, contributing to its overall strength and stability. The microstructural analysis confirmed these findings, showing a denser soil matrix and stronger inter-particle bonds. This study concludes that ESP is a promising alternative to traditional soil stabilizers, offering environmental benefits by utilizing waste material and reducing the need for cement and lime. The use of ESP in soil stabilization contributes to sustainable construction practices and presents a viable solution for improving the performance of clay soils in construction.
Keywords: Clay; Eggshell powder; Environmental impact; Shear strength; Soil stabilization